Processos educativos na Congada em Catalão (GO): Reflexões sobre o lugar do corpo para o aprender-ensinar-aprender dos saberes socioculturais - Carvalho, Eloane Aparecida Rodrigues (2023)
Both education and the cultural and religious manifestation of the congadas are conceived in this thesis as social practices, and are therefore expressed through actions and thoughts that establish knowledge as they reconstruct and reaffirm various conceptions of the world, society, group and subject. In this sense, we are dealing with processes of meaning in the world that are re-elaborated by educational practices in the context of social relations. To this end, we are looking at these educational practices promoted within the congadas in the city of Catalão, located in the state of Goiás. Because of their expressiveness and representativeness, we approached and dialogued with those who make up the Terno Vilão Santa Efigênia, popularly known as Vilão Rosa. In short, we started from the premise that the congadeiros are recognized as a collective that interrelates education and cultures in a process of reaffirming their socio-cultural memories. Thus, we understand the importance of corporeality and voice [oralitura] for the historical constitution of this group, as they constitute values and symbols that, at the same time, rework and resignify their ways of thinking-knowing-doing in spaces-times. We also infer that these practices, especially those promoted in another educational space, weave together the construction of their collective identity, their cultural awareness, as well as the construction of tradition, which have been systematized gradually and are reaffirmed on a daily basis through a variety of symbols, rituals and meanings. This discussion is based on the following questions: what is the importance of the body in the learning-teaching-learning process within the Terno Vilão Santa Efigênia? And what are the contributions of this educational process to thinking about another perspective of formal Brazilian education? Furthermore, this research is based on epistemological and theoretical assumptions based on decolonial thinking. As far as methodology is concerned, we opted for participant research, emphasizing the ethnographic perspective with a qualitative bias; moreover, the investigation was consolidated by interdisciplinarity focused on the Human Sciences. It was in being with the congadeiros of Vilão Rosa that our reflections were developed, taking their memories and stories as references, as well as their experiences in the processes of teaching-learning-teaching their collectively constructed knowledge. In this way, together, we built up our sources of understanding about the elements that make up this social practice, while dialoguing with our experiences within schools and formal education classrooms. We believe that this epistemic-theoretical-methodological journey has allowed us to infer that learning-teaching-learning, when promoted in a more shared and horizontalized way, tends to promote learning that stems from the interweaving of all the senses of the human body, in which seeing, hearing, feeling, touching, experiencing and sharing are part of the teaching-learning processes. It is in this integration [unity] and interaction that we can say that the more the body and mind are 'vibrating' in the same direction, the more learning can be built and shared, both with the group and with other collectives. Therefore, with sensitive eyes and attentive listening, the congadas have come to be seen as another formative space, made up of educational processes that both influence and promote the permanence of this tradition, while recognizing its memories of resistance and valuing its socio-cultural identities.